Evaluasi Kinerja Pelayanan UtilitasTerhadap Transportasi Publik di Kota Semarang - Aldio GemaPenta Mahadika; Fitriyah .; Puji Astuti (Journal of Politic and Government Studies, 2014)
ABSTRACKThe requirement for cheap, safety and comfortable of public transportation are reflection ofsome people’s hope. Semarang City Office of Transportation with Semarang City Government tries topursue people’s dreams, by creating a new transportation modes in Semarang City. BRT (Bus RapidTransit) is a breakthrough in order to achieve people’s expectation on cheap, safety and comfortablepublic transportation service. Therefore it’s necessary to evaluate performance of BRT Trans Semarangpublic service, in order to determine quality of BRT Trans Semarang public service.The population of this research are BRT Trans Semarang public service users, at three corridorthat is operated by providers of BRT Trans Semarang. Main indicators of this research consisted of:physical appearances, reliability ,empathy , security guarantee, and accessbility. Data collectiontechniques of this research used quiestionner that distributed throughout all BRT Trans Semarangcorridor, with number sample of population were 60 respondens.The priorities that must be considered from the result of this research at hygiene and punctualityproblem. Those problems expected to be a concern for increasing BRT Trans Semarang public servicequality. Therefore people can use BRT Trans Semarang as priority public transport users.Keywords: Public Service, Mass Transport, Main Priority , physical appearance, reliability , empathy ,security guarantee and accessbility